Visual perception and drawing relationship in art education - Turkmenoglu, Dilek (ELSEVIER SCIENCE BV, 2012)
Today, a wide research area in perception psychology has been established on how individuals perceive and transfer the outside world through drawings that are considered as a measure of artistic development in art education. In this respect, the study focuses on supportability of programs and exercises included in drawing courses in fine arts education with data specific to the students' visual perception processes. The purpose of the study is to a contribute a flexible program suggestion taking into account individual differences in terms of perception issues and to support students' participation in this program with solutions about themselves. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Ayse Cakir Ilhan
Keywords: visual perception; cognition; self awareness; drawings; art education; Art